2014
DOI: 10.15517/rbt.v54i2.13867
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus thuringiensis in caterpillars and associated materials collected from protected tropical forests in northwestern Costa Rica

Abstract: Abstract. Bacillus thuringiensis (Bt) synthesizes crystalline inclusions that are toxic to caterpillars (Lepidoptera) and other orders of invertebrates. Materials associated with 37 caterpillars from 16 species, collected while feeding on 15 different species of host plants in dry, cloud and rain forests located in the Área de Conservación Guanacaste in northwestern Costa Rica, were examined for the presence of Bt. From a total of 101 derived samples, 25 Bt isolates were cultured: 56% from host plant leaves, 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Whether this dose is similar to a dose H. subflexa and H. virescens might encounter in a natural environment is difficult to evaluate. The few attempts to measure the density of Bt spores in nature646566 have documented a very patchy distribution.…”
Section: Methodsmentioning
confidence: 99%
“…Whether this dose is similar to a dose H. subflexa and H. virescens might encounter in a natural environment is difficult to evaluate. The few attempts to measure the density of Bt spores in nature646566 have documented a very patchy distribution.…”
Section: Methodsmentioning
confidence: 99%
“…Bt has been isolated from the phylloplane in natural or artificial ways [ 34 , 42 , 43 , 44 ]. It has been shown that Bt can reach this niche by rain splash from the soil to lower leaves [ 31 ], from soil as a result of being carried by germinating seeds [ 43 ], from animal feces such as those from insects or birds [ 34 , 36 ], and from dead insects [ 34 ].…”
Section: Niches Occupied By Btmentioning
confidence: 99%
“…Zhang et al [ 36 ] showed the presence of Bt in the intestinal tract of chickens, with the duodenum being the main portion colonized; moreover, it was verified that these animals kept releasing the bacterium through their feces for a certain time, even after removal of Bt from the diet. Similarly to vertebrates, Bt has been also isolated from fecal pellets of non-susceptible caterpillars from forests of conservation areas [ 44 ]. In another report, Bt germination in the alimentary tract was demonstrated in different invertebrates (e.g., earthworms), with sporulation occurring after defecation [ 8 ].…”
Section: Niches Occupied By Btmentioning
confidence: 99%